The age of the source rock and its source facies for the migrated oil in rock samples from Novaya Zemlya - Kúld, Ingi Thór Hallgrimson (2009)
In this work I have in detailed tried to determine the age of the source rock that is responsible for petroleum impregnation in onshore samples from Novaya Zemlya. I have worked with a selected set of 6 samples. Pilot investigations of nearly 90 year old rock samples of Devonian to Carboniferous age, sampled by Professor Olaf Holtedahl in 1921 from the archipelago of Novaya Zemlya, which spans on a regional scale some 500 km, has shown that several rock samples were impregnated with migrated bitumen, i.e. oil of surprisingly uniform maturity and organic facies in particular when bearing in mind the large lateral distances. While these samples were originally sampled for fossils, I found irrefutable proof of hydrocarbon migration episodes. The TOC and HI values of in-situ organic matter of the samples today reflect deep burial and overmature conditions, with values mostly in the range of 1-4.5 % of TOC and HI values in as low as 1–6. I conclude that the source rock potential of these rocks show a paleopotential realized possibly already during the Ural-Novaya Zemlya – Permian Orogeny. Yet, extracts in the range of 0.37-2.83 mg/rock show on Iatroscan typically 48-70 % saturated hydrocarbons, 4-14 % aromatic hydrocarbons and 15-47 % polar compounds (resins plus asphaltenes). GC-FID data show normal alkanes and “Unresolved Complex Mixture” (UCM) which reflects several migration episodes of oil into the “burned out carbonaceous/silty lithologies” with intermittent periods of biodegradation, and most likely water washing cf. low contents of aromatic hydrocarbons. Inferred source rock facies from GC-FID and GC-MS data reflect that the source rock is likely to be a marine shale with some influence of land plant derived organic matter, i.e. containing mainly kerogen type II, but with some type III. Land derived organic material is indicated by the occurrences of oleanane and heavy δ13C stable carbon isotope ratios. The unknown hydrocarbon source rock is therefore suggested to be a distal, predominantly marine shale with ...